A case study on misuse of company's Confidential Information in Malaysia: Suggestions for improvement - Hassan, Halyani; Abd Jalil, Juriah (2020)
Directors and employees are individuals who involved in the course of company’s business and would inevitably expose themselves to company’s confidential information. At present there are in existence legal provisions imposing duties upon the directors and employees for the purpose of protecting the company’s confidential information. In addition, the employees would normally be subjected to non-disclosure agreement upon their employment. The progress of the present technology has exposed company’s information at a high risk to be manipulated by individuals who involved in the company. This paper aims to discuss the viability of the present safeguard in protecting the company’s confidential information. The research intends to analyse decided cases on the approach adopted in determining whether there is misused or misappropriation of company‘s confidential information by the directors or the employees. The discussion would also focus on whether the non-disclosure of company’s confidential information would still be relevant when the directors or employees leave the company. In suggesting improvement for the present scenario it would be pertinent to analyse as well case laws from different jurisdiction. This study would be significant to ensure that the company’s confidential information is being sufficiently protected so that the company would remain competitive and dynamic.